WellGrown: Aplikasi Pencegah Stunting Melalui Pengaturan Pola Makan Berbasis Design Thinking - Dian Resvina; I Ketut Gede Suhartana (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
Child stunting is a chronic nutritional issue that hampers physical and cognitive development, particularly during the first 1,000 days of life (HPK). In Indonesia, although the stunting rate declined from 24.4% in 2021 to 21.6% in 2022, it remains a major public health challenge. Currently, 30.8% of children under five are stunted, 10.2% suffer from wasting, and 48.5% of pregnant women are anemic. In response, the Indonesian government has set a national target to reduce the stunting rate to 14% by 2024, using a cross-sectoral approach focused on the HPK period. The root causes of stunting include inadequate nutritional intake, limited knowledge, and improper parenting practices. To support these efforts, technological innovation plays a vital role. The WellGrown mobile application, developed using the Design Thinking approach, aims to assist prospective parents by offering accessible health and nutrition guidance for pregnant women and children up to two years of age. With this strategy, monitoring and evaluation during the HPK period can become more efficient. The System Usability Scale (SUS) score for WellGrown is 82.5, reflecting its high usability and user satisfaction.